Upper Ordovician Thylacocephala (Euarthropoda, Eucrustacea) from Bohemia indicate early ecological differentiation. (26th April 2021) - Van Roy, Peter; Rak, Štěpán; Budil, Petr; Fatka, Oldřich
Abstract: Thylacocephala is a clade of marine bivalved euarthropods generally considered to belong to Eucrustacea, although their affinities within this group remain unsettled. Detailed thylacocephalan anatomy and tagmosis is poorly known, and the majority of taxa have been described based only on the valves of the carapace. While some thylacocephalans are considered to have been fully nektic, others probably had a nekto‐benthic mode of life. The group makes its last appearance in the Upper Cretaceous of Lebanon, while the previously oldest definite record is from the Silurian of Wisconsin, USA. This paper describes two new thylacocephalans, Pseudoprotozoea irenae gen. et sp. nov. and Bohemiacaris libori gen. et sp. nov. from the Sandbian (Upper Ordovician) Letná Formation of Bohemia (Czech Republic). Apart from the carapaces, both fossils preserve some evidence of the appendages. Remarkably, even though the newly described taxa represent the oldest unequivocal thylacocephalans, their carapaces display several characters most similar to those of Mesozoic groups. Whether these similarities reflect true close relationships and Ordovician origins for these groups or are only the result of convergent evolution is uncertain. Regardless, the new finds show that ecological differentiation between fully nektic and nekto‐benthic lifestyles was probably achieved early in the evolution of Thylacocephala.